Digital Marketing and Competitive Advantage: Moderated by Digital Transformation - Joko, Joko; Riswanto, Ari; Kurniawan, Dede (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to determine the development of competitive advantage studies from a digital marketing perspective as a variable influencing factor, besides that the digital transformation variable is also placed as a moderating variable. The approach used is descriptive quantitative using a questionnaire as a data collection tool which is distributed to 205 SMEs in West Java Province, Indonesia. Structural Equation Modeling with simple moderation is used in analyzing data that has been collected, which has previously been tested for validity by Confirmatory Factor Analysis. This study found that digital transformation variables are able to mediate the effect of digital marketing on the competitive advantage of SMEs in West Java province, Indonesia. This is something new or new, because there has been no previous research that places digital transformation as a moderator variable for the influence of digital marketing on competitive advantage. This research has the opportunity to conduct more in-depth studies on larger units of analysis or in more complex industries, so that more interesting and useful things will be found in scientific development efforts, especially in the field of management science.